Inhibitory effects of food additives derived from polyphenols on staphylococcal enterotoxin A production and biofilm formation by Staphylococcus aureus. Issue 12 (2nd December 2017) - Shimamura, Yuko; Hirai, Chikako; Sugiyama, Yuka; Shibata, Masaharu; Ozaki, Junya; Murata, Masatsune; Ohashi, Norio; Masuda, Shuichi
Abstract: In this study, we examined the inhibitory effects of 14 food additives derived from polyphenol samples on staphylococcal enterotoxin A (SEA) production and biofilm formation by Staphylococcus aureus . Tannic acid AL (TA), Purephenon 50 W (PP) and Polyphenon 70A (POP) at 0.25 mg/mL and Gravinol®-N (GN), Blackcurrant polyphenol AC10 (BP), and Resveratrol-P5 (RT) at 1.0 mg/mL significantly decreased SEA production by S. aureus C-29 ( p < 0.05). TA, GN, BP, and RT significantly inhibited the expression of the sea gene in S. aureus C-29 ( p < 0.05), while suppression attempts by PP and POP proved unsuccessful. After result analysis, it can be derived that TA, GN, BP, and RT inhibit the production of SEA. Of the six samples, each one significantly inhibited biofilm formation ( p < 0.05). Food additives derived from polyphenols have viability to be used as a means to inhibit the enterotoxin production and control the biofilm formation of foodborne pathogens. Abstract: : Food additives derived from polyphenols inhibit staphylococcal enterotoxin A production and biofilm formation by Staphylococcus aureus .